Emanuel Liais: a scientist of two continents - Muniz Barreto, Luiz (1994)
In the middle of the 18th Century, the necessity to explore a new land induced the Portuguese Crown to send to the Colony many geographers and cartographers, such as Parigai, Cieira, Pithon, Basco, Alpoin (Carvalho, 1985). It was a crude beginning of Astronomy and Geophysics in Brazil. However, the efforts to establish a regular scientific practice with those specialists were insufficient to be considered as the birth of scientific research. It was necessary to create a true national scientific institution and the conditions for the entry on the scene of the main actor in our story: Emmanuel Liais. These notes intend to analyze his importance in the History of Geomagnetism.